A comprehensive overview of advanced oxidation process assisted mono-ethanolamine degradation in aqueous phase: Current advances and future challenges. Issue 3 (June 2022) - Khan, Atif; Mahmood, Hamayoun; Yasin, Saima; Moniruzzaman, Muhammad; Iqbal, Tanveer
Abstract: AOPs have showed considerable potential in the purification and treatment of water, especially for the removal of naturally occurring toxins, emerging pollutants, pesticides, and other harmful substances. It entails the generation of sufficient hydroxyl radicals to affect water purification. In a water treatment, the AOPs can significantly increase the breakdown of mono-ethanolamine (MEA), a recalcitrant pollutant with a main amine group. This research examines innovative AOPs for the treatment of MEA in the aqueous phase in depth. This paper gives a systematic assessment of MEA degradation mechanisms and pathways, as well as a complete examination of process parameters that influence degradation rate, such as pH, temperature, and MEA doses. Ozonation, UV, Fenton, and Plasma treatments, as well as hybrid processes such as per-oxone processes, catalytic ozonation, UV/Ozonation, UV/catalysis, UV/chlorination, and photo-Fenton processes, have all recently been reported as AOPs for MEA degradation. This review would also aid researchers in gaining a better understanding of critical operating parameters and laying the groundwork for the development of commercially viable solutions. Finally, this study concludes with some challenges and a brief assessment of future developments in this field of research. Graphical Abstract: ga1 Highlights: A comparison of conventional and AOP approaches for MEA degradation in the aqueous phase has been explored. Explanation of the synergistic effects of combining several AOPs. Different AOPs for MEA treatment in wastewater were compared in terms of treatment efficiency. For treating MEA in the aqueous phase, AOPs are the most promising and effective oxidation technology. The current challenges, issues, and research directions are discussed.